Akt2 is required for hepatic lipid accumulation in models of insulin resistance - Leavens, Karla F. (2009)
Insulin drives the global anabolic response to nutrient ingestion, regulating both carbohydrate and lipid metabolism. Previous studies have demonstrated that Akt2/protein kinase B is critical to insulin’s control of glucose metabolism, but its role in lipid metabolism has remained controversial. Here we show that Akt2 is required for hepatic lipid accumulation in obese, insulin-resistant states induced by either leptin-deficiency or high fat diet feeding. Lep(ob/ob) mice lacking hepatic Akt2 failed to amass triglycerides in their livers, associated with and most likely due to a decrease in lipogenic gene expression and de novo lipogenesis. However, Akt2 is also required for steatotic pathways unrelated to fatty acid synthesis, as mice fed high fat diet had reduced liver triglycerides in the absence of hepatic Akt2 but did not exhibit changes in lipogenesis. These data demonstrate that Akt2 is a requisite component of the insulin-dependent regulation of lipid metabolism during insulin resistance.